PEMIDANAAN ANAK DALAM PERSPEKTIF KEADILAN RESTORATIF - Hadibah Zachra Wadjo (Faculty of Law, Universitas Pattimura, 2016)
The Indonesian Penal Code system enters a new phase in its development. One of the reforms existing in the Indonesian Penal Code is the regulation of criminal law in perspective and the achievement of justice to the improvement and restoration of the situation after the events and processes of criminal justice known as restorative justice which is different from retributive justice (emphasizing justice on retaliation ) And restitutive justice (emphasizing justice on compensation). Children are part of the citizens who must be protected because they are a generation of nation that in the future will continue the leadership of the Indonesian nation. Each child in addition must get a formal education such as school, also must get a moral education so that they can grow into a figure that is useful for the nation and state. In accordance with the provisions of the Convention on the Rights of the Child ratified by the Indonesian government through Presidential Decree No. 36 of 1990, then also set forth in Law No. 4 of 1979 on Child Welfare and Law No. 23 of 2002 On Child Protection and Law No. 11 of 2012 on the Criminal Justice System of the Child which all present general principles of child protection, namely non-discrimination, best interests for children, survival and growth